2017
DOI: 10.1158/0008-5472.can-16-2482
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of Pediatric Supratentorial High-grade Glioma Reveal How Cell-of-Origin Influences Tumor Development and Phenotype

Abstract: High-grade glioma (HGG) is a group of primary malignant brain tumors with dismal prognosis. Whereas adult HGG has been studied extensively, childhood HGG, a relatively rare disease, is less well-characterized. Here, we present two novel platelet-derived growth factor (PDGF)-driven mouse models of pediatric supratentorial HGG. Tumors developed from two different cells of origin reminiscent of neural stem cells (NSC) or oligodendrocyte precursor cells (OPC). Cross-species transcriptomics showed that both models … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…In order to verify our hypothesis, we tried to study the interconnection between anatomic location and genetic biomarkers in our patient cohort. Beforehand, many papers published have put forward the cell origin theory underlying possible relationship between these two factors [ 20 , 21 ]. Many groups have successfully developed computational methods to predict glioma genetic alterations based on location features [ 18 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to verify our hypothesis, we tried to study the interconnection between anatomic location and genetic biomarkers in our patient cohort. Beforehand, many papers published have put forward the cell origin theory underlying possible relationship between these two factors [ 20 , 21 ]. Many groups have successfully developed computational methods to predict glioma genetic alterations based on location features [ 18 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…All GSC cultures were derived from anonymized grade IV, nonrecurrent glioblastoma samples obtained from patients undergoing surgical resection at Uppsala University Hospital in accordance with protocols approved by the regional ethical review board (2007/353) and following patients' written consent . Sixty IDH1 wild‐type cultures were used at passages 5–15 and were tested negative for mycoplasma using two different methods, MycoAlert Mycoplasma Detection kit (Lonza, Basel, Switzerland) and a PCR‐based method as previously described . For details, see supplementary materials, Supplementary materials and methods.…”
Section: Methodsmentioning
confidence: 99%
“…We know from previous studies in the lab using mouse models of GBM that the developmental state of the cell of origin can influence both the molecular subtype of the developed tumor and its ability to establish a SF culture (Jiang et al, ; Sreedharan et al, ). We have found that a more differentiated glial origin produced GBM cells that were difficult to maintain in culture compared to a neural stem cell‐like origin (Sreedharan et al, ). Differences in maintainability due to cell of origin has also been reported by others (Ledur et al, ).…”
Section: Discussionmentioning
confidence: 99%